Gamified Strategies for Teaching Construction Planning - Regina Maria Cunha Leite; Lynn Rosalina Alves Gama; Larissa da Silva Paes Cardoso; Matina Leite Vieira Lima; Hugo Meijon Morêda Neto (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
This study examines a gamified interface that can be accessed over the Web and aims to develop social and cognitive skills in students enrolled in undergraduate civil engineering and technical building courses who will ultimately work in construction companies. The methodological approach chosen is Design Science. This study is aligned with the generalization phase of a gamified solution for construction workers. To support the activities developed in the classroom, considering aspects of context, educational objectives, required skills, desired behaviors, and interactions, the gamified system was evaluated by 7 teachers and students, who focused on the functionalities, usability of the system (System Usability Scale - SUS) and promotability (Net Promoter Score - NPS). It also helps future technicians and engineers learn the importance of meeting deadlines, planning, and organizing the dynamics of the work that needs to be done, negotiating, and making decisions as a group, and reading the instructions to perform the tasks that need to be done in planning and budgeting for construction sites. The approach that the model takes to teach construction planning and budgeting is new and can captivate students, as well as encourage leadership and teamwork among the participants.